Narrativas da autoconstrução: perspectivas para o campo de conhecimento da arquitetura - Danielle de Fátima Cunha (2023)
Aiming to answer the question “what do the narratives of self-builders reveal to the field of architectural knowledge about producing space?”, we did a bibliographical research in order to better define the meaning and implications of the concepts used in its formulation, namely field of architectural knowledge and self-construction. Based on this theoretical repertoire and a corpus of eleven open interviews with self-builders from peripheral neighborhoods in brazilian city of Conselheiro Lafaiete, we then applied Bardin’s content analysis technique to those narratives. Through this process we formulated theoretical reflections around the topics: territory, constructive practices, time and income, culture and agents, otherness, self-determination. Those reflections composed a reading that allows us to advance the understanding of self-construction, a predominant phenomenon in the production of Brazilian urban space, as well as formulate an approach to the ways the field of architectural knowledge filters and hierarchizes information. Consequently, this allows us new perspectives on the insertion of the architect in the production of urban space and the formation of this field of knowledge.